1,25-Dihydroxyvitamin D increases calmodulin binding to specific proteins in the chick duodenal brush border membrane. - Bikle, D D (1985)
In previous studies we demonstrated that the biologically active vitamin D metabolite 1,25-dihydroxyvitamin D [1,25(OH)2D] increased the calmodulin (CaM) content of chick duodenal brush border membranes (BBM) without increasing the total cellular CaM content. Therefore, we evaluated the binding of CaM to discrete proteins in the BBM and determined whether 1,25(OH)2D could influence such binding. We observed one major and several minor CaM-binding bands on autoradiograms of sodium dodecyl sulfate polyacrylamide gels incubated with [125I]CaM. The major band had a molecular weight of 102,000-105,000. It bound CaM even in the presence of EGTA, but not in the presence of trifluoperazine or excess nonradioactive CaM. The administration of 1,25(OH)2D increased the apparent binding of CaM to this protein as assessed by densitometry of the autoradiogram. This increase in CaM binding coincided with the increased ability of the same BBM vesicles to accumulate calcium. Cycloheximide in doses that markedly reduced the incorporation of [35S]methionine into BBM proteins did not reduce the ability of 1,25-dihydroxyvitamin D3 to stimulate either calcium uptake by the BBM vesicles or CaM binding to the 102,000-105,000-mol-wt protein. These results suggest that 1,25(OH)2D administration increases the CaM content of duodenal BBM by increasing the ability of a 102,000-105,000-mol-wt protein to bind CaM. This mechanism may underlie the ability of 1,25(OH)2D to stimulate calcium movement across the intestinal BBM.